Enhancing Local Food Industry: Production of “Sehati” Marning Corn in Bantaeng Regency - Lestari, Mega Fia; Syaiful, Syaiful; Irwan , Muhammad; Sitanggang, Boy Chandra; Hermansyah, Hermansyah; Odilia Valentine; Aras, Neny Rasnyanti M; Ratlalan, Roberth Marshall; Abidin, Zainal; Supu, Abd Rachman (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The local food processing business is essential to the Indonesian economy. Lumpangan Village in Bantaeng Regency, South Sulawesi, has great potential due to the Small and Medium Enterprises (SME) product "SEHATI," which manufactures Marning Corn. However, the need on sunshine for drying limits production, reducing output during the rainy season. To address this issue, the Akademi Komunitas Industri Manufaktur Bantaeng community service programme strives to improve corn product quality through the use of mechanical dryers and the education of workers on Good Manufacturing Practices (GMP). Methodology: This program's methodology comprises collaborating with village officials, observing SMEs, developing solutions, implementing the community service programme, and assessing the program's success. Results: Observations show that mechanical dryers are successful in resolving drying problems, and GMP education enhances product quality. Conclusions: The service program was successful in raising the marning corn production by UMKM "SEHATI" and establishing the program as a long-term initiative. In addition, the program received the full support of village officials by the successful in overcoming production constraints during the rainy season through the purchase of corn dryers and Good Manufacturing Practice (GMP) education. Limitations: Prior to deployment, the primary drawback was a reliance on dry weather conditions. Contributions: This programme makes a substantial contribution, with the expectation that its long-term success will help to create other SMEs in Lumpangan Village and increase the quality of Marning corn products through better drying technology and worker education.